Language Learning Strategies: How the Islamic Learners in IAIN Palopo Learn English - Muhammad Iksan (Institut Agama Islam Negeri Palopo, 2021)
This study intended to describe the Language Learning Strategies that the English learners use in IAIN Palopo. This descriptive study involved 86 learners from the English Language Education Study Program as the research subject. The data in this study is gained using Adapted SILL Questionnaire, which Rebecca Oxford developed. Through the questionnaire, the study found that the English learners use all the categories of Language Learning Strategies, i.e., Memory Strategies, Cognitive Strategies, Compensation Strategies, Metacognitive Strategies, Affective, and Social Strategies. Furthermore, the level of the learners' LLSs use is categorized into Medium level. Metacognitive Strategies are the most popular strategies used by the learners (29%), followed by Affective Strategies (20,9%). In contrast, the Compensation Strategies (8%) become the least used strategies by the learners.